Implementation of project management principles in spanish residential developments - Pellicer, Eugenio; Victory, Richard (International Journal of Strategic Property Management, 2010)
Urban development of land and subsequent residential development of buildings are closely related to construction industry. Within the industry, project management is widely applied in Anglo‐Saxon countries. Nevertheless, the results obtained from the literature review conducted did not find how project management is taken into consideration in land and property management. Furthermore, this project management approach is seldom implemented in the Spanish construction industry, even in the private sector. The traditional rigidity and protectionism of the industry, along with the peculiarities of the Spanish Building Law, create a scenario where innovation is difficult to attain. Although, there is a promising future for small to medium sized project management firms to provide a very wide range of services to private clients. This paper shows how the implementation of project management principles can be attempted for residential developments in the Mediterranean Coast of Spain. An inductive approach is used as methodology. After explaining the real state process for the Spanish market, a basic outline for the implementation of project management is proposed. Project and client risk assessment, preliminary questionnaires, stages and steps, company organisation related to professional expertise, procurement strategies and contractual relationships are displayed. Finally, the model is tested by two characteristic case studies. First Published Online: 18 Oct 2010